TINJAUAN KELENGKAPAN PENGISIAN FORMULIR PERSETUJUAN TINDAKAN KEDOKTERAN SECTIO CAESAREA DI PRIMAYA EVASARI HOSPITAL - Indah Kristina; Muhamad Abdul Fatah (APIKES Bhumi Husada Jakarta, 2023)
ABSTRACT Approval for medical action is the approval given by the patient or his closest family after receiving a complete explanation regarding the medical or dental action to be performed on the patient. recording of approval for medical action as evidence that the patient agrees to the action to be taken and must be filled in completely because it can be used as legal evidence in the event of a claim from the patient. This study was conducted to identify standard operating procedures (SOPs) for completing the approval form for sectio caesarea medical action, identify the completeness of filling out the approval form for planned and emergency sectio caesarea medical actions, identify the factors causing incomplete completion of the consent form for medical action at Primaya Evasari Hospital. The research method used is descriptive method with a sample of 103 medical treatment consent forms. The results of the study, standard operating procedures for filling out approval forms for medical actions are available, completeness of filling out approval forms for medical actions 64% are completely filled out and 36% are incomplete, factors that cause incomplete filling of consent forms for medical actions include not knowing that standard operating procedures are available for filling 20% , did not receive socialization of filling out the 20% form, did not understand how to revise 60%, the impact of incomplete filling in the consent form Medical action is that it cannot make valid evidence in the event of a lawsuit. Keywords: completeness of filling out the consent form for medical action.